Pendekatan SFBC (Solutiom Focused Brief Counseling) Teknik Scarlling Question Dalam Konseling Individu Untuk Meningkatkan Motivasi Berprestasi Korban Bullying - yasmin qurrotu aini; Indah lestari (STKIP PGRI SUMENEP, 2023)
From the research conducted by the researcher, there were cases of students being bullied by their classmates, which resulted in their performance dropping because they felt anxious while taking lessons. Bullying is a behavior that usually occurs in schools, usually someone does bullying because they feel they are the most powerful or powerful. As a result, someone who is a victim of bullying feels anxious, threatened, insecure and calm, and can reduce the victim's achievement motivation. The approach that can be used is the Solution Focused Brief Counseling approach with the scarling question technique. Objectives of the Solution Focused Brief Counseling approach is one of the approaches used in school settings. Counselors can use it to solve problems with students, but this approach places more emphasis on the solution, not the problem. Finding solutions quickly and precisely to overcome the problems faced by students. By using the scarling question technique, the counselee can take actions that can bring about changes according to what they want.